Growth velocity in elementary school children with iron deficiency anemia after iron therapy - Dina Lyfia; Melda Deliana; Hakimi Hakimi; Nelly Rosdiana; Bidasari Lubis (Paediatrica Indonesiana, 2009)
Background Iron supplementation in children with iron deficiencyanemia could decrease the incidence of stunting.Objective To study the effect of iron therapy on growth velocityin children with iron deficiency anemia.Methods A randomized clinical trial study was conducted atLabuhan Batu on November 2006 to May 2007. Iron deficiencyanemia was diagnosed if there were anemia, with mean corpuscular hemoglobin concentration <31 %, red cell distribution width index > 220, and Mentzer index> 13. Elementary school children (6-12 year old) with iron deficiency anemia were randomly assigned either to iron therapy group (children were given 6 mg iron/kg/day) or to placebo group for 3 months.Results Among 300 children recruited, there were 125 children,who suffered from iron deficiency anemia. After one month ofiron therapy, means of hemoglobin concentration were 12.4 g/dl in iron group and 11.7 g/dl in placebo group. There was a significant increase of height in iron group (129.9 (SD 7.58) em vs. 132.2 (SD 7.23) em) and in placebo (130.8 (SD 8.78) em vs. 128.7 (SD 8. 79) em), However, no significant difference was found in the mean of growth velocity between placebo and iron groups (2.1 (SD 0.01) em vs. 2.0 (SD 0.9) em.Conclusion There is a significant increase in height, but nosignificant difference between both groups in growth velocity.